2023
DOI: 10.3390/atmos14061007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lichens and Mosses as Biomonitors of Airborne Microplastics

Abstract: The atmosphere is an important pathway for microplastic (MP) transport; however, observations are limited, as traditional sampling methods are generally labor-intensive. Biological monitors (biomonitors) have been widely used as a simple alternative to determine the abundance or presence of anthropogenic pollutants. Here, we compared the effectiveness of co-located lichen and moss species as biomonitors of the atmospheric deposition of microplastics. Samples of the epiphytic lichen Evernia prunastri and the ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The water samples were subsequently vacuum filtered onto cellulose filter papers (Watman Grade 1, 1001-090, 11 µm) with a diameter of 90 mm, and the filters stored in glass Petri dishes. The filter papers (n = 50, 1 filter paper per 100 mL) were examined for MPs under a stereomicroscope (Eurotek OXTL101TUSB equipped with an MDCE-5C digital camera) following a fivecriteria method: unnatural colour, material homogeneity, particle resiliency, reflective surfaces, and limited fraying [43][44][45][46]. Fibres and fragments that met at least two criteria were considered anthropogenic and photographed [55], and further verified as plastic using a hot needle [56,57].…”
Section: Microplastic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The water samples were subsequently vacuum filtered onto cellulose filter papers (Watman Grade 1, 1001-090, 11 µm) with a diameter of 90 mm, and the filters stored in glass Petri dishes. The filter papers (n = 50, 1 filter paper per 100 mL) were examined for MPs under a stereomicroscope (Eurotek OXTL101TUSB equipped with an MDCE-5C digital camera) following a fivecriteria method: unnatural colour, material homogeneity, particle resiliency, reflective surfaces, and limited fraying [43][44][45][46]. Fibres and fragments that met at least two criteria were considered anthropogenic and photographed [55], and further verified as plastic using a hot needle [56,57].…”
Section: Microplastic Analysismentioning
confidence: 99%
“…However, only a few studies have evaluated the deposition of MPs using leaves of higher plants such as shrubs [39], pine needles [40], tree species [41], and lettuce [42]. In addition, a number of studies have focused on the use of cryptogams such as mosses and lichens for monitoring the deposition of airborne MPs [43][44][45][46][47][48][49]. While some researchers have employed Robinia pseudoacacia L. leaves for investigating the deposition of potentially toxic elements (PTEs) from the atmosphere [50,51], no study has yet explored its potential for the analysis of atmospheric MPs, particularly regarding TWPs.…”
Section: Introductionmentioning
confidence: 99%
“…Micro- and nanoplastics (MNPs) are gaining increasing attention currently. Since the first evidence of microplastics (MPs) in human feces in 2019, they have been found in various human biological samples such as saliva, sputum, liver, breastmilk, lung, and blood. This suggests that MPs can be transported throughout the body via circulation. In vitro experiments suggest that MNP toxicity to human cells may result from membrane damage, oxidative stress, immune response, and genotoxicity. Monomers and additives (e.g., stabilizers and plasticizers) may leach from the MNPs inside the organism, exposing the tissues to hazardous chemicals such as phthalates and bisphenol A .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in a study focused on the use of native mosses for the estimation of anthropogenic microfiber in terrestrial environments, Roblin and Aherne [11] adopted a methodology based on the visual identification of relatively large mfs (>30 µm, according to the authors' data). The same approach was adopted by Jafarova et al (2023) [12] to compare native mosses and lichens for the assessment of the atmospheric deposition of anthropogenic MPs. However, the uncertainty associated with the age of thalli is a limitation in the use of native species [13].…”
Section: Introductionmentioning
confidence: 99%
“…A large body of literature demonstrated that in moss and lichen individual peculiar traits favor from time to time the accumulation/retention of pollutants as metal(loid)s and PAHs. However, very little is known about the interactions between mfs and plant biomonitors [10] and limited data are available comparing different biomonitors in the same context [12]. Considering that the visual identification of mfs can evidence only relatively large debris, the presence of the net used in transplants could substantially affect their accumulation.…”
Section: Introductionmentioning
confidence: 99%